1999
DOI: 10.1111/j.1530-0277.1999.tb04355.x
|View full text |Cite
|
Sign up to set email alerts
|

CSF Monoamine Metabolite and Beta Endorphin Levels in Recently Detoxified Alcoholics and Healthy Controls: Prediction of Alcohol Cue‐Induced Craving?

Abstract: These results are inconclusive about the role of monoaminergic dysregulation in recovering alcoholics. They also question the utility of these CSF measures to predict alcohol cue reactivity in patients who have been sober at least 1 month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
4
11
0
Order By: Relevance
“…These findings are in accordance with the results of one other study on plasma HVA in abstinent alcoholics (Fulton et al, 1995), whereas studies on alcoholism examining CSF HVA instead of plasma HVA produced inconsistent results (Heinz et al, 1999;Petrakis et al, 1999;Lappalainen et al, 1999;Virkkunen et al, 1996), most likely caused by the difficulties of determining central HVA concentrations through HVA in CSF.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are in accordance with the results of one other study on plasma HVA in abstinent alcoholics (Fulton et al, 1995), whereas studies on alcoholism examining CSF HVA instead of plasma HVA produced inconsistent results (Heinz et al, 1999;Petrakis et al, 1999;Lappalainen et al, 1999;Virkkunen et al, 1996), most likely caused by the difficulties of determining central HVA concentrations through HVA in CSF.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast to HVA in the cerebrospinal fluid (CSF-HVA) plasma HVA is a potential indicator of central dopaminergic neuronal activity (Amin et al, 1992) and can therefore be used as a tool to study the psychopathology of addictive disorders. So far only few studies have tried to elucidate the role of HVA in human alcoholism with contradictory results (Heinz et al, 1999;Gabel, 1995;Petrakis et al, 1999;Lappalainen et al, 1999;Fulton et al, 1995;Virkkunen et al, 1996). Fulton et al (1995) could show in a case control study with a sufficiently large study population that plasma HVA was significantly lower in alcoholic patients (n ¼ 83) compared to 69 healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with previous reports that alcoholism affects CSF HVA levels (Roos and Silfverskiöld, 1973;Kato et al, 1979;Goldman et al, 1992;Takahashi et al, 1974;Major et al, 1977;Fujimoto et al, 1983;Roy et al, 1991a;Virkkunen et al, 1996;Fils-Aime et al, 1996;Petrakis et al, 1999). Roy et al (1991a) reported that depressed subjects with alcoholism had significantly lower concentrations of HVA than never depressed subjects with alcoholism.…”
Section: Biological Findingssupporting
confidence: 83%
“…Low CSF HVA may have more to do with psychopathology related to alcoholism as opposed to mood disorder biology. Our finding is consistent with studies that suggest that dopaminergic mechanisms play a part in the biology of alcohol use disorders, including mechanisms of alcohol dependence and withdrawal (Diana et al, 1993;Weiss et al, 1996;Weiss and Koob, 1991;Koob, 1992;Noble, 1996;Wiesbeck et al, 2000;Fromme and D'Amico, 1999;Nevo and Hamon, 1995;Roos and Silfverskiöld, 1973;Kato et al, 1979;Goldman et al, 1992;Takahashi et al, 1974;Major et al, 1977;Fujimoto et al, 1983;Roy et al, 1991a;Virkkunen et al, 1996;Fils-Aime et al, 1996;Petrakis et al, 1999;Samson et al, 1990;Valenzuela and Harris, 1997;Robinson and Berridge, 1993;VavrousekJakuba et al, 1992;Quarfordt et al, 1991;Modell et al, 1993;Grace, 2000).…”
Section: Biological Findingssupporting
confidence: 79%
See 1 more Smart Citation